Isolation of archaeal viruses with lipid membrane from Tengchong acidic hot springs - Feng, Xi; Li, Yanan; Tian, Chang; Yang, Wei; Liu, Xinyu; Zhang, Changyi; Zeng, Zhirui (Frontiers in Microbiology, 2023)
Archaeal viruses are one of the most mysterious parts of the virosphere because of their diverse morphologies and unique genome contents. The crenarchaeal viruses are commonly found in high temperature and acidic hot springs, and the number of identified crenarchaeal viruses is being rapidly increased in recent two decades. Over fifty viruses infecting the members of the order Sulfolobales have been identified, most of which are from hot springs distributed in the USA, Russia, Iceland, Japan, and Italy. To further expand the reservoir of viruses infecting strains of Sulfolobaceae, we investigated virus diversity through cultivation-dependent approaches in hot springs in Tengchong, Yunnan, China. Eight different virus-like particles with were detected in enrichment cultures, among which five new archaeal viruses were isolated and characterized. We showed that these viruses can infect acidophilic hyperthermophiles belonging to three different genera of the family Sulfolobaceae, namely, Saccharolobus, Sulfolobus, and Metallosphaera. We also compared the lipid compositions of the viral and cellular membranes and found that the lipid composition of some viral envelopes was very different from that of the host membrane. Collectively, our results showed that the Tengchong hot springs harbour highly diverse viruses, providing excellent models for archaeal virus-host studies.